Deconstructing poloxamer and poloxamine block copolymers to access poly(ethylene glycol) and poly(propylene oxide)-based thermoresponsive polymers. Issue 6 (2nd June 2020) - Hong, Jeonghui; Oh, Junki; Khan, Anzar
Abstract: Poloxamer (Pluronic ® ) and poloxamine (Tetronic ® ) are commercially important block copolymers composed of polypropylene oxide (PPO) and polyethylene glycol (PEG) segments. Due to the difference in chemical polarity of the two blocks, the copolymers exhibit amphiphilicity and thermally induced aggregation behavior in aqueous solutions. The present work shows that block copolymer architecture is not necessary to achieve an amphiphilic character in PPO and PEG-based polymers. Instead a simple molecular tweaking by adding a very short hydrophilic or hydrophobic side-chain allows for attaining amphiphilicity and consequential thermoresponsiveness in PEG and PPO-rich polymers.